Body size and multiple myeloma mortality: a pooled analysis of 20 prospective studies. (23rd May 2014) - Teras, Lauren R.; Kitahara, Cari M.; Birmann, Brenda M.; Hartge, Patricia A.; Wang, Sophia S.; Robien, Kim; Patel, Alpa V.; Adami, Hans‐Olov; Weiderpass, Elisabete; Giles, Graham G.; Singh, Pramil N.; Alavanja, Michael; et al.
Summary Multiple myeloma (MM) is a rare but highly fatal malignancy. High body weight is associated with this cancer, but several questions remain regarding the aetiological relevance of timing and location of body weight. To address these questions, we conducted a pooled analysis of MM mortality using 1·5 million participants (including 1388 MM deaths) from 20 prospective cohorts in the National Cancer Institute Cohort Consortium. Proportional hazards regression was used to calculate pooled multivariate hazard ratios (HRs) and 95% confidence intervals (CIs). Associations with elevated MM mortality were observed for higher early‐adult body mass index (BMI; HR = 1·22, 95% CI: 1·09–1·35 per 5 kg/m2) and for higher cohort‐entry BMI (HR 1·09, 95% CI: 1·03–1·16 per 5 kg/m2) and waist circumference (HR = 1·06, 95% CI: 1·02–1·10 per 5 cm). Women who were the heaviest, both in early adulthood (BMI 25+) and at cohort entry (BMI 30+) were at greater risk compared to those with BMI 18·5 ≤ 25 at both time points (HR = 1·95, 95% CI: 1·33–2·86). Waist‐to‐hip ratio and height were not associated with MM mortality. These observations suggest that overall, and possibly also central, obesity influence myeloma mortality, and women have the highest risk of death from this cancer if they remain heavy throughout adulthood.